Новые виды пресноводных моллюсков (Bivaivia, Cycladidae) фауны СССР - Стадниченко, А.П. (Вестник зоологии, 1980)
Descriptions and drawings of four Cycladidae species new for science are given: Euglesa (Cingulipisidium) juliae S t a d n i c h e n k o, sp. n., E. (Euglesa) crimeana Stadnichenko, sp. n., E. (Euglesa) dymy S t a d n i c h e n k o, sp. n. and E. (Ca- sertiana) alexandri Stadnichenko, sp. n.